2021
DOI: 10.1016/j.pmedr.2021.101558
|View full text |Cite
|
Sign up to set email alerts
|

Improving lung cancer screening: An equitable strategy through a tobacco treatment clinic

Abstract: Annual screening with low dose chest tomography has been adopted for those at high risk to aid in the early detection of lung cancer. In addition to screening, it is recommended that such persons receive evidence-based smoking-cessation. However, both lung cancer screening and evidence-based smoking-cessation strategies are underutilized in the US. We review the impact of a dedicated Tobacco Treatment Clinic (TTC), delivering evidence-based smoking cessation strategies, on lung cancer screening enrollment. Pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…based upon age and smoking history, to high-quality decision support materials on LCS. 22 We found that the training session significantly improved quitline staffs' knowledge of LCS from baseline, and that quitline staff thought that connecting quitline callers to LCS education was acceptable, feasible, and appropriate. Our findings show that overall, quitline staff had low levels of baseline knowledge of LCS, indicating that there is a need for training about lung cancer and LCS so they can educate quitline callers, particularly about the eligibility criteria and the potential benefits and harms of LCS.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…based upon age and smoking history, to high-quality decision support materials on LCS. 22 We found that the training session significantly improved quitline staffs' knowledge of LCS from baseline, and that quitline staff thought that connecting quitline callers to LCS education was acceptable, feasible, and appropriate. Our findings show that overall, quitline staff had low levels of baseline knowledge of LCS, indicating that there is a need for training about lung cancer and LCS so they can educate quitline callers, particularly about the eligibility criteria and the potential benefits and harms of LCS.…”
Section: Discussionmentioning
confidence: 80%
“…Tobacco quitlines can play a critical role in connecting quitline callers, many of whom are eligible for LCS based upon age and smoking history, to high‐quality decision support materials on LCS 22 . We found that the training session significantly improved quitline staffs' knowledge of LCS from baseline, and that quitline staff thought that connecting quitline callers to LCS education was acceptable, feasible, and appropriate.…”
Section: Discussionmentioning
confidence: 89%
“…Of these 40 articles, the majority addressed cancer screening, with most (n = 13) focusing on reducing inequities in colorectal cancer (CRC) screening. One article addressed lung cancer screening, 19 four articles addressed breast cancer screening with mammography [20][21][22] or sameday biopsy. 23 Seven articles addressed cervical cancer screening [24][25][26][27][28][29] or follow-up colposcopy.…”
Section: Resultsmentioning
confidence: 99%
“…Overall, outreach by professional healthcare providers and lay educators alike appears to improve screening rates, including minority groups 25,29,30 . In addition, results suggest that strategies designed to increase access to cancer screening can reduce disparities in guideline‐concordant screening 19,23 . However, additional evidence is needed to clarify which strategies are likely to be most effective for building engagement in different communities.…”
Section: Discussionmentioning
confidence: 99%
“…All patients who attended the Tobacco Treatment and Cancer Screening Clinic (TTCSC), which has been previously described [ 24 ], between January 2021 to December 2021 were screened for potential inclusion. Screening consisted of a member or members of the TTCSC interdisciplinary team reviewing patient charts prior to their clinical appointment.…”
Section: Methodsmentioning
confidence: 99%